Analysis of Risk Factors of Quality of Snacks Food Sold in Town Squares of Magetan, Ngawi, Ponorogo and Madiun - Denok Indraswati; Djoko Windu P. Irawan; Lilis Prihastini; Sigit Gunawan; Bejo Utomo (Humanistic Network for Science and Technology (HNST), 2018)
Guidelines on Hygiene Sanitation Requirements for Snack Food through Ministry of Health Decree No. 942 / Menkes / SK / VII / 2003 has been issued, including its supporting regulations. The national movement towards safe, qualified and nutritious snacks food by the government through the Vice President of the Republic of Indonesia has been declared since January 31, 2011. But the incidence of national poisoning that occurred in 2014 based on group ofcauses factors, the food ranked the highest. The purpose of this research is to analyze the risk factors of physical, chemical, and microbiological contamination on snacks food. Type of observational research is cross sectional approach. Object / population is all snack foods sold in Town squares of Magetan, Ngawi, Ponorogo and Madiun. The selected sample is siomay snack food. Analysis technique used is descriptive percentage. Bivariate analysis is done to get an idea of whether there is a relationship between independent variables with other independent variables, and between each independent variable with the dependent variable. In the analysis, it is used cross tabs and Chi-square test. Multivariate analysis is used to analyze the role of independent variables together with dependent variable. The result of physical examination is generally got bad result, chemical examination got good result and microbiology examination of germs resulted bad result, so food of siomay snacks is generally declared not worth consuming. Keywords: Snacks food, Physical, Chemistry, Microbiology quality